The seminar goes to work: Towards a theory of collaborative literacy. Issue 4 (August 2020) - Smith, Ann Kowal; Jaussen, Capria; Nestor, Karen R.
The research and practice are clear: the humanities develop empathy, sensibility, and other individual skills critical to successful employment. But, they also support the development of collective skills that empower productive teams and workplaces. This article explores the collective impact of narrative literature through the lens of an innovative workplace-based learning program. The program uses facilitated conversations about literature to invite colleagues at all levels to practice questioning assumptions, listening to different voices, and connecting to new ideas and to each other. Examining data from over 800 participants, the authors provide scholarly and practice-based evidence that literature discussions support otherwise elusive workplace dynamics. The results establish the link between shared human experience and workplace quality, as colleagues learn to be and work together . In addition, the concept of collaborative literacy that emerges from this study promises a new approach to learning in multiple non-traditional settings and in the academy itself.